Using Near-Surface Photogrammetry Assessment of Surface Roughness (NSPAS) to assess the effectiveness of erosion control treatments applied to slope forming materials from a mine site in West Africa - Campbell, Stephanie; Simmons, Robert W.; Rickson, R. Jane; Waine, Toby W.; Simms, Daniel M. (Elsevier, 2018)
Geo-spatial studies are increasingly using photogrammetry technology because the cost of the equipment is becoming cheaper, the techniques are accessible to non-experts and can generate better quality topographic data than traditional approaches. NSPAS (Near-Surface Photogrammetry Assessment of Surface Roughness) was developed to quantify the micro-topographic changes in ground surface roughness caused by simulated rainfall, to better understand the comparative erodibility of two non-soil and one soil slope forming materials from a mine in West Africa. This innovative approach creates DEMs (digital elevation models) using image pairs acquired by near-surface stereo photogrammetry (<300 m), to measure surface roughness within Leica Photogrammetry Suite 2011 (LPS) in ERDAS Imagine software and ESRI Arc-GIS. NSPAS can readily quantify aggregate breakdown processes across a 0.02 m2 surface by accurately detecting 0.84 mm to 2.49 mm changes in surface topography. The methodology is advantageous to micro-scale (<1 cm2) studies that require a high number of accurate DEMs, because it will produce image pairs even when the target does not have contrasting surface features in shot, which can be a constraint for the automated technique Structure from Motion. This paper demonstrates how NSPAS is more suitable to assess erosion from slope forming materials that do not have a high content of large rocks (>2 mm) at the surface. With further development NSPASS has the capability to be used in many other types of geospatial investigations.
Keywords: Near-Surface Photogrammetry Assessment of Surface Roughness (NSPAS); Surface roughness; Erosion; Slope forming materials